INTEGRATING TECHNOLOGY SKILLS WITH INTERPERSONAL COMPETENCIES TO ENHANCE GRADUATE EMPLOYABILITY IN MALAYSIAN TECHNICAL UNIVERSITY NETWORKS - Wong, Reynold; Saraih, Ummi Naiemah (Finansha: Journal of Sharia Financial Management, 2024)
The Fourth Industrial Revolution (4IR) has heightened the demand for graduates equipped with a balanced integration of technological skills and interpersonal competencies to meet the evolving needs of the workforce. This concept paper explores the critical role of technology skills as a moderating factor in enhancing the impact of self-efficacy, soft skills, and personality traits on graduate employability within the Malaysian Technical University Network (MTUN). By examining these relationships, the study provides a framework to align graduate training with the demands of technology-driven industries. The findings emphasize the importance of embedding both technical and interpersonal skills into educational curricula to equip graduates for dynamic, technology-centric workplaces. This paper offers actionable insights to guide curriculum reforms, ensuring graduates are holistically prepared to thrive in the rapidly evolving global economy shaped by 4IR advancements.